Digestive proteases and in vitro protein digestibility in bagrid catfishMystus nemurus(Cuvier and Valenciennes 1840) - Rahmah, Sharifah; Hashim, Roshada; El-Sayed, Abdel-Fattah M. (Wiley, 2024)
Indexed by WOS/Scopus/ERA